1995
DOI: 10.1136/gut.36.5.731
|View full text |Cite
|
Sign up to set email alerts
|

Novel germline APC gene mutation in a large familial adenomatous polyposis kindred displaying variable phenotypes.

Abstract: The APC gene is mutated in the germline of people from families where there is a predisposition to develop polyposis coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
9

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 22 publications
3
50
0
9
Order By: Relevance
“…7,[38][39][40][41] Mutations at the 5' end of the APC gene are predicted to result in extremely short and presumably unstable truncated proteins. Consequently, these mutations might act as a null allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[38][39][40][41] Mutations at the 5' end of the APC gene are predicted to result in extremely short and presumably unstable truncated proteins. Consequently, these mutations might act as a null allele.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition to genotype and phenotype heterogeneity, patients with an identical mutation can exhibit phenotype variability, probably due to a modifying locus or environmental factors. [6][7][8] Due to the inherent difficulty in detecting gene deletions, interstitial 5q deletions that encompass the APC gene have been identified in very few FAP patients. [9][10][11][12][13][14][15][16] So far, large deletions account for about 2% of the identified germline mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, researchers have identified correlations between specific mutational locations and the existence of extracolonic manifestations (Olschwang et al, 1993, Eccles et al, 1996, the number of colorectal adenomas (Scott et al, 1995), age at diagnosis of FAP and age at onset of colorectal cancer Friedl et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have shown both inter-and intrafamilial phenotypic variations among patients carrying the identical mutation Paul et al 1993;Varesco et al 1993;Giardiello et al 1994;van der Luijt et al 1995;Scott et al 1995), some studies have indicated clear genotype-phenotype correlations between the location of the APC gene mutation and the characteristic manifestations of FAP. These include the number of polyps Spirio et al 1993;Gayther et al 1994;Scott et al Germline mutations of the APC gene in Korean familial adenomatous polyposis patients Friedl et al 1996), the age of onset and death Caspari et al 1994;Gayther et al 1994;Scott et al 1995;Friedl et al 1996), the presence of congenital hypertrophy of the retinal pigment epithelium (CHRPE) Caspari et al 1995), and the occurrence of desmoid tumors (Caspari et al 1995;Davies et al 1995;Scott et al 1995;Dobbie et al 1996;Eccles et al 1996). Thus, the evidence strongly suggests that there are different functional mutations within the APC gene with respect to the position of the mutation.…”
Section: Introductionmentioning
confidence: 99%